Putative Membrane-Bound Transporters MFSD14A and MFSD14B Are Neuronal and Affected by Nutrient Availability - Lekholm, Emilia; Perland, Emelie; Eriksson, Mikaela M.; Hellsten, Sofie V.; Lindberg, Frida A.; Rostami, Jinar; Fredriksson, Robert (Frontiers in Molecular Neuroscience, 2017)
Characterization of orphan transporters is of importance due to their involvement in cellular homeostasis but also in pharmacokinetics and pharmacodynamics. The tissue and cellular localization, as well as function, is still unknown for many of the Solute carriers (SLCs) belonging to the Major facilitator superfamily (MFS) Pfam clan. Here we have characterized two putative novel transporters MFSD14A (HIAT1) and MFSD14B (HIATL1) in the mouse central nervous system and found protein staining throughout the adult mouse brain. Both transporters localized to neurons and MFSD14A co-localized with the Golgi marker Giantin in primary embryonic cortex cultures, while MFSD14B staining co-localized with an endoplasmic retention marker, KDEL. Based on phylogenetic clustering analyses we predict both to have organic substrate profiles, and possible involvement in energy homeostasis. Therefore we monitored gene regulation changes in mouse embryonic primary cultures after amino acid starvations and found both transporters to be upregulated after 3 h of starvation. Interestingly, in mice subjected to 24 h of food starvation, both transporters were downregulated in the hypothalamus, while Mfsd14a was also downregulated in the brainstem. In addition, in mice fed a high fat diet, upregulation of both transporters was seen in the striatum. Both MFSD14A and MFSD14B were intracellular neuronal membrane-bound proteins, expressed in the Golgi and Endoplasmic reticulum, affected by both starvation and high fat diet to varying degree in the mouse brain.